FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KUALITAS TIDUR PADA PASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISIS DI RUMAH SAKIT TARAKAN JAKARTA - Pius, Enggus Subarman; Herlina, Santi (Fakultas Ilmu Kesehatan, 2019)
Sleep is an activity that involves the arrangement of the central nervous, endocrine, cardiovascular peripheral nervous, respiratory and Musculoskeletal, sleep disorders often occur in patients with end-stage renal failure. Problems with sleep disorders experienced by about 5080% of patients who undergo the therapy Hemodialisis. The average patient undergoing chronic renal failure Hemodialisis having problems on the quality of sleep. With increasing numbers semakian kejdian renal failure it will be growing patients undergoing therapy Hemodialisis. From the results of a survey conducted by researchers at the hospital tarakan terdapa chronic renal failure patient 90 undergoing Hemodialisis, this number is calculated from December 2013February 2014. Researchers want to know the relationship of companion ailments, psychological stress, environment and kelelahaan with the quality of sleep in patients with chronic renal failure undergoing Hemodialisis in Jakarta Tarakan hospital Hemodialisis. Methods used is descriptive with sample 40 respondents taking with total sampling techniques and observation guided by kuessioner as instruments. A research done in earn comorbidities such 79,3 %, psychological stress 92,3 %, environment 91,7 %, and fatigue 100 %. Disease penuerta, psychological stress, environment and fatigue very influential on quality sleep patient kidney failure chronicle underwent Hemodialisis. The high influence of companion ailments, psychological stress, the environment, and the fatigue of sleep quality chronic renal failure patients undergoing Hemodialisis, hence the need for a serious handling of the health care personnel to be able to minimize the faktor that can affect the quality of sleep is chronic renal failure patients undergoing Hemodialisis at Jakarta Tarakan hospital